A reklámok időbeli és terjedelmi korlátai - Pribula, László (Debreceni Jogi Műhely, 2006)
Advertising forms are considerable parts of economic activities, the costs of which constitute a growing portion of the expenses of a given enterprise. The mass-appearance of advertisements has altered the relationship between consumers and advertisers, it has restructured consumption habits and the importance of the advertising media. Advertising law defines the restrictions that have to be observed during business and advertising activities. The regulation of advertising is characterized by an approach focusing on content. However, in some cases the legislator also considered it important to determine the form of advertising besides its content. In the case of most advertising media there are only few regulations on form. The Media Act (Act I of 1996) dedicates a whole chapter to restrictions on advertising. The most important part of the Media Act is the regulation of the way commercials can be shown. The regulation of maximum advertising time, the type of programmes which are suitable for advertising and the period of time that can pass between commercials is given priority.